Integrating maqāsid shariah literacy into the financial capability framework: Evidence from Islamic family financial planning - Dea Aryandhana Mulyana Haris; Ulumuddin Nurul Fakhri; Firmansyah Firmansyah; Muhammad Ridho Al-Firdausi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study examines the influence of maqāsid shariah literacy, institutional trust, and Islamic financial literacy on Islamic family financial planning competence. Previous studies on Islamic financial planning have largely focused on technical financial literacy while overlooking ethical-spiritual dimensions and institutional trust within the financial capability framework. This study addresses this theoretical gap by integrating maqāsid-based literacy into the financial capability framework, offering a distinct value-oriented perspective rarely explored in prior empirical research. Using a quantitative approach, data were collected from Muslim households in West Java, Indonesia, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that maqāsid shariah literacy and institutional trust significantly influence Islamic family financial planning competence, whereas Islamic financial literacy does not show a significant effect. The study theoretically extends the financial capability framework by incorporating maqāsid-oriented and ethical spiritual dimensions into Islamic financial behavior and family financial planning discourse